Peptidomimetic‐based identification of FDA‐approved compounds inhibiting IRE1 activity. (11th June 2020) - Doultsinos, Dimitrios; Carlesso, Antonio; Chintha, Chetan; Paton, James C.; Paton, Adrienne W.; Samali, Afshin; Chevet, Eric; Eriksson, Leif A.
Abstract : Inositol‐requiring enzyme 1 (IRE1) is a bifunctional serine/threonine kinase and endoribonuclease that is a major mediator of the unfolded protein response (UPR) during endoplasmic reticulum (ER) stress. Tumour cells experience ER stress due to adverse environmental cues such as hypoxia or nutrient shortage and high metabolic/protein‐folding demand. To cope with those stresses, cancer cells utilise IRE1 signalling as an adaptive mechanism. Here, we report the discovery of the FDA‐approved compounds methotrexate, cefoperazone, folinic acid and fludarabine phosphate as IRE1 inhibitors. These were identified through a structural exploration of the IRE1 kinase domain using IRE1 peptide fragment docking and further optimisation and pharmacophore development. The inhibitors were verified to have an impact on IRE1 activity in vitro and were tested for their ability to sensitise human cell models of glioblastoma multiforme (GBM) to chemotherapy. We show that all molecules identified sensitise glioblastoma cells to the standard‐of‐care chemotherapy temozolomide (TMZ). Abstract : FDA‐approved drugs and small peptides were identified as potent IRE1 inhibitors through a systematic in silico and in vitro exploration. The compounds block XBP1 mRNA splicing by IRE1 in vitro and at subtoxic doses sensitise glioblastoma cells to chemotherapy. The findings provide insights on utilising the inhibition of the unfolded protein response (UPR) as a modality in cancer treatment.